A new logarithmic profile model and optimization design of cylindrical roller bearing. Issue 5 (10th August 2015) - Cui, Li; He, Yafei
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to find a new logarithmic profile model of cylindrical roller bearing, which is expected to avoid edge effect and allow a straight portion on the roller considering uniform pressure distribution and easier manufacturing. Design/methodology/approach – A new logarithmic cylindrical roller profile model using three parameters is proposed. Contact model between roller and rings and quasi-static model of roller bearing are given to obtain contact pressure distribution and solved by multi-grid and Newton–Raphson method. Optimization of modified reference rating life model of the roller bearing is proposed by using genetic algorithms. Findings – Under heavy load or tilting moment conditions, modified reference rating life of cylindrical roller bearing may increase greatly by optimization of three design parameters using the new logarithmic profile model. Originality/value – The results of the present paper could aid in the design of logarithmic profile of cylindrical roller bearing and increase fatigue life of cylindrical roller bearing.